Personal Data Protection in Technological Developments Era - Ardan Biantoro, Farrel (International Journal of Law Social Sciences and Management, 2024)
This research examines the legal impacts of the development of Artificial Intelligence (AI) technology. This paper employs a juridical normative research method. Data sources include legislative regulations and policies related to the discussed legal issues. Artificial intelligence aims to understand that AI technology not only creates tools and systems capable of performing tasks once done by humans but also enters realms that carry profound legal implications. With its ability to process and analyze vast amounts of data, legal questions arise concerning individual privacy, system security, legal accountability, and more. The legal challenges in the development of AI technology are highly complex and layered, encompassing various aspects from data privacy to legal responsibility, ethics, security, and reliability. Existing regulations often struggle to keep pace with AI innovation, creating legal gaps that need prompt attention